Themes in Islamic Da’wah by Malaysian Preachers on TikTok: Preliminary Study - Salinayanti, Salim; Ting, Su Hie; Siti Haslina, Hussin (2024)
The proliferation of social media has significantly expanded the reach of Islamic da’wah (call or invitation to Islam). TikTok has become the most recent yet prominent platform due to its ability to disseminate short videos efficiently. In the rhetorical religious genre, religious orators employ various approaches to persuade the audience and their da’wah content often revolves around specific themes. This preliminary study investigated the thematic content of Islamic da’wah videos of ten famous Malaysian preachers on TikTok, each video being under two minutes in duration. Through a comprehensive thematic analysis, three primary themes were identified: religious teaching, spiritual reflection and moral guidance. The finding revealed that a single video could encompass multiple themes, with religious teaching emerging as the most prevalent theme. Additionally, the finding indicated that the preachers' da'wah revolves around worshiping Allah SWT and is characterised by two dimensions: self-reflection and interaction with others, except for moral guidance, which solely focuses on addressing others. In terms of platform of dissemination, this study discovered that TikTok serves as a platform for the dissemination of meaningful and instructive content related to Islam, catering to the diverse needs of its users. One implication f this is the potential for TikTok to contribute to the shaping of religious discourse and practices among its users, influencing their beliefs and behaviours.